2021
DOI: 10.1016/j.ypmed.2021.106540
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing breast imaging services during the COVID pandemic: A survey of breast imaging facilities within the Breast Cancer Surveillance Consortium

Abstract: The COVID-19 pandemic disrupted breast cancer screening and diagnostic imaging in the United States. We sought to evaluate how medical facilities prioritized breast imaging services during periods of reduced capacity or upon re-opening after closures. In fall 2020, we surveyed 77 breast imaging facilities within the Breast Cancer Surveillance Consortium in the United States. The survey ascertained the pandemic's impact on clinical practices during March–September 2020. Nearly all facilities (97%) reported clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
7
18
0
Order By: Relevance
“…While these local and state mandates were highly variable, all six of our institutions were at least temporarily closed for routine screening. This is in keeping with a recent survey by the Breast Cancer Surveillance Consortium, which revealed that 97% of surveyed United States breast imaging facilities were temporarily closed or operated at reduced capacity between March 2020 and September 2020 ( 8 ).…”
Section: Introductionsupporting
confidence: 87%
“…While these local and state mandates were highly variable, all six of our institutions were at least temporarily closed for routine screening. This is in keeping with a recent survey by the Breast Cancer Surveillance Consortium, which revealed that 97% of surveyed United States breast imaging facilities were temporarily closed or operated at reduced capacity between March 2020 and September 2020 ( 8 ).…”
Section: Introductionsupporting
confidence: 87%
“…Furthermore, diagnostic studies were prioritized over screening mammography. 5 Interestingly, the 11% decline in mammography observed at our institution is less than the near 90% decline observed nationally. 6 …”
Section: Discussionmentioning
confidence: 53%
“…As others have noted, breast cancer treatment saw a relatively lower decline in volume compared to mammograms at our institution suggestive that treatment for breast cancer was differentially prioritized over breast cancer screening in the context of severely limited healthcare resources. 5 …”
Section: Discussionmentioning
confidence: 99%
“…The dire predictions and early evidence that cancer screening dramatically declined prompted investment and capacity for “return to screening” initiatives and patient prioritization policies (Joung et al 2022; Sprague et al 2021). However, most early predictions focused on the initial decline, as opposed to the subsequent rebound, and so did most of the early research.…”
Section: Discussion/conclusionmentioning
confidence: 99%